Pengembangan Sistem Informasi Geografi Bencana Alam Pada Kabupaten Madiun Berbasis Web Menggunakan Metode Build and Fix - Ezra Gayu; Pradityo Utomo; Dwi Nor Amadi (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2018)
Development Natural Disaster Information Geografis System is a website service utilizing digital map service. To facilitate the Regional Disaster Management Agency (BPBD) and the Community of Madiun Regency in providing and receiving information about the occurrence of Natural Disasters in Madiun District, the need for the application of information systems. The information system can display the points where the Natural Disasters occur. With the Information System, everyone can see the location of the map of the disaster occurrence area along with the description of the area. in this study developed a "Natural Disaster Information System at Madiun district". System development using Build and Fix method, because it is considered fast in making the system. The built system can be expected to assist BPBD officers in performing their duties. So that the system built must have the ability to form information accurately the occurrence of natural disasters. Therefore, the disaster information system in Madiun district has been tested using blackbox method, with 100% system success rate.Â Keywords : Web, Madiun District, Natural Disaster, Information Geografis System, Build and Fix, Blackbox